2019
DOI: 10.1111/eva.12822
|View full text |Cite
|
Sign up to set email alerts
|

The preference–performance relationship as a means of classifying parasitoids according to their specialization degree

Abstract: Host range in parasitoids could be described by the preference–performance hypothesis (PPH) where preference is defined as host acceptance and performance is defined as the sum of all species on which parasitoid offspring can complete their life cycle. The PPH predicts that highly suitable hosts will be preferred by ovipositing females. However, generalist parasitoids may not conform to this hypothesis if they attack a large range of hosts of varying suitability. Under laboratory conditions, we tested the PPH … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 97 publications
0
25
0
Order By: Relevance
“…1) [9,11,38]. In the wild, both species are found infecting a wide range of aphid species although their host ranges differ, with A. ervi more specialized on aphids in the Macrosiphini tribe and L. fabarum on the Aphidini tribe [39,40]. Experimental evolution studies in both species have shown that wild-caught populations can counter-adapt to cope with aphids and the defenses of their endosymbionts, and that the coevolutionary relationships between parasitoids and the aphids' symbionts likely fuel diversification of both parasitoids and their hosts [41][42][43].…”
Section: Introductionmentioning
confidence: 99%
“…1) [9,11,38]. In the wild, both species are found infecting a wide range of aphid species although their host ranges differ, with A. ervi more specialized on aphids in the Macrosiphini tribe and L. fabarum on the Aphidini tribe [39,40]. Experimental evolution studies in both species have shown that wild-caught populations can counter-adapt to cope with aphids and the defenses of their endosymbionts, and that the coevolutionary relationships between parasitoids and the aphids' symbionts likely fuel diversification of both parasitoids and their hosts [41][42][43].…”
Section: Introductionmentioning
confidence: 99%
“…Such a scenario does not seem to be a likely explanation for acceptance of the milkweed aphid by A. certus in our study, however. This parasitoid species has a relatively low egg load (see also Hopper et al, 2013;Monticelli et al, 2019a) and our dissections from the choice studies clearly show that eggs that could have been laid into the suitable soybean aphid were instead laid into the unsuitable milkweed aphid. We believe rather that A. certus attacks unsuitable hosts as reflection of the fact that it is a generalist aphid parasitoid (Hopper et al, 2017a).…”
Section: Discussionmentioning
confidence: 81%
“…Soybean aphid is not known to sequester toxic compounds, while milkweed aphid sequesters toxic secondary metabolites (cardenolides) from its host plants which are toxic against natural enemies (Mooney et al, 2008) including parasitoids (Desneux et al, 2009a). However, milkweed aphid has been reported to be attacked by various parasitoid species, including Aphelinus abdominalis, Aphidius ervi, Aphidius colemani, Binodoxys communis, Lysiphlebus testaceipes, and Diaeretiella rapae (Benelli et al, 2014;Colvin & Yeargan, 2013;Cortez-Madrigal et al, 2016;Desneux et al, 2009a;Hartbauer, 2010;Helms et al, 2004;Monticelli et al, 2019a;Vaz et al, 2004;Wyckhuys & Heimpel, 2007). We used A. certus in our study because (a) it is known as a parasitoid of soybean aphid, which has been shown to be suitable (Frewin et al, 2010;Heimpel et al, 2010;Hopper & Diers, 2014;Hopper, et al, 2017a;Kaser & Heimpel, 2018) and (b) it is known to attack milkweed aphid despite the low level of suitability of this aphid species (Kaser, 2016).…”
Section: The Study Systemmentioning
confidence: 99%
“…One 608 functional explanations for a lower number of OR genes in L. fabarum is that the A. 609 ervi strain sequenced of was derived from several field strains that parasitized 610 different hosts on different host plants, and the ability to parasitize a broader host 611 range could select for more OR genes (Monticelli et al 2019). 612 613 Chemosensory: Ionotropic chemosensory receptors (IRs) 614…”
Section: Chemosensory: Odorant Receptors (Ors) 601mentioning
confidence: 99%